KUALITAS FISIK SILASE PAKAN KOMPLIT BERBAHAN DASAR JERAMI SORGUM (Sorghum bicolor (L) moench) DENGAN TARAF YANG BERBEDA - Syahruddin, Syahruddin (Gorontalo Journal of Equatorial Animals, 2023)
ABSTRACTSorgum is a cereal plant that can grow well on dry land. Sorgum is a source of food and animal feed. Sorghum has a high nutritional value and is used to replace other sources of food. This study aims to know the physical quality of complete silage made from sorgum straw with different levels. This study employs a completely randomized design with 4 treatments and 4 replications. The treatments are P1 (60% sorgum straw + 30% natural grass + 10% concentrate), P2 (70% sorgum straw + 20% natural grass + 10% concentrate), P3 (80% sorgum straw + natural grass + 10% concentrate), and P4 (90% sorgum straw + 0% natural grass + 10% concentrate). Parameters measured are physical quality (odor, color, and texture) and pH of silage. The finding shows that complete feed silage made from sorgum straw with different levels has no significant effect (P0.05) on the physical quality but has a significant effect (P0.01) on pH. The physical quality of complete feed silage is classified as a good silage category, and the silage pH shows a good category value.Keywords: sorgum straw; silage; physical quality; pH